The tomb of shadows / 3. - Lerangis, Peter (Seven wonders ;, 2014)
Teens Jack, Marco, Aly, and Cass begin a quest to find seven pieces of Atlantis' power that were hidden long ago and that will, if returned to Atlantis, save them from certain death due to the genetic abnormality that also gives them superior abilities.